2013
DOI: 10.1093/nar/gkt307
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-mediated Period2 induction delays the phase of circadian rhythm

Abstract: Glucocorticoid (GC) signaling synchronizes the circadian rhythm of individual peripheral cells and induces the expression of circadian genes, including Period1 (Per1) and Period2 (Per2). However, no GC response element (GRE) has been reported in the Per2 promoter region. Here we report the molecular mechanisms of Per2 induction by GC signaling and its relevance to the regulation of circadian timing. We found that GC prominently induced Per2 expression and delayed the circadian phase. The overlapping GRE and E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 69 publications
3
78
2
1
Order By: Relevance
“…FS caused a significant increase in RNA expression of Fkbp5, Per1, and Sgk1, which is consistent with their well-known responsiveness to glucocorticoids (17)(18)(19)(20). The hnRNA levels for Per1 and Sgk1 peaked at 30 min, whereas Fkbp5 hnRNA levels reached their maximal levels later at 60 min.…”
Section: Discussionsupporting
confidence: 80%
“…FS caused a significant increase in RNA expression of Fkbp5, Per1, and Sgk1, which is consistent with their well-known responsiveness to glucocorticoids (17)(18)(19)(20). The hnRNA levels for Per1 and Sgk1 peaked at 30 min, whereas Fkbp5 hnRNA levels reached their maximal levels later at 60 min.…”
Section: Discussionsupporting
confidence: 80%
“…These results might indicate a differential responsiveness of the different elements of the hepatic circadian clock to the glucocorticoids. However, this could depend on the model employed, since it has shown the presence of a GRE in Cry1 gene in mice and humans (Reddy et al 2007), and a synchronization of Per2 gene by a glucocorticoid treatment (Cheon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Functional glucocorticoid response elements (GREs) in the promoter regions of Per1, Per2, and E4bp4 have also been reported as possible factors in the signaling mechanisms of molecular clocks [26, 27], and the expression of Rev - erbα in the liver has been reported to decrease in response to glucocorticoid treatment via GREs [28]. In our most recent study, we also confirmed that dexamethasone (an analog of corticosterone) induced phase entrainment of peripheral PER2 rhythms in the liver, kidney, and submandibular gland [20].…”
Section: Stress-induced Entrainment Of the Circadian Clockmentioning
confidence: 99%